2020
DOI: 10.1038/s41467-020-15438-y
|View full text |Cite
|
Sign up to set email alerts
|

Downsizing of animal communities triggers stronger functional than structural decay in seed-dispersal networks

Abstract: Downsizing of animal communities due to defaunation is prevalent in many ecosystems. Yet, we know little about its consequences for ecosystem functions such as seed dispersal. Here, we use eight seed-dispersal networks sampled across the Andes and simulate how downsizing of avian frugivores impacts structural network robustness and seed dispersal. We use a trait-based modeling framework to quantify the consequences of downsizing—relative to random extinctions—for the number of interactions and secondary plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 74 publications
3
58
0
Order By: Relevance
“…This finding is also consistent with a recent simulation study showing that defaunation, i.e. the size-structured extinction of avian seed dispersers, leads to a rapid decay in seed-dispersal distances across a range of tropical seed-dispersal networks (Donoso et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is also consistent with a recent simulation study showing that defaunation, i.e. the size-structured extinction of avian seed dispersers, leads to a rapid decay in seed-dispersal distances across a range of tropical seed-dispersal networks (Donoso et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The loss of species from a community is often uneven across traits or ecological strategies. For example, losses are often biased towards large-bodied species (Santini et al 2017) leading to the decline or loss of long-distance seed dispersal as well as altering the quantity of seeds dispersed (McConkey et al 2012, Donoso et al 2020.…”
Section: Validity Of the Analysesmentioning
confidence: 99%
“…Human‐induced alteration of composition of animal communities, such as changes in the number of individuals or species has been shown to impact seed dispersal patterns (Fontúrbel et al 2015). In particular, LDD has been significantly reduced by defaunation or species loss (Donoso et al 2020). Previous work has demonstrated that the loss of megafauna (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, lateral nutrient movement by terrestrial mammals has been estimated to have reduced by >90% following the downsizing of mammals over the last 10,000 years (Doughty, Roman, et al, 2016; Hempson et al., 2017) while global microbe dispersal in faeces has decreased seven‐fold, possibly increasing independent microbial evolution through an ‘island biogeography effect’, which is believed to increase the emergence of infectious diseases (Doughty et al., 2020). Likewise, significant reductions in seed dispersal have been shown following changes to populations of large frugivorous bird species (Donoso et al., 2020; Jordano et al., 2007; Wotton & Kelly, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…At present, dispersal models that assess biological dispersal of seeds, nutrients and microbes across a broad suite of taxa often use generalised mass‐based scaling parameters for gut passage time (e.g. Donoso et al., 2020; Doughty et al., 2020; Doughty, Roman, et al, 2016; Hempson et al., 2017; Pires et al, 2018; Sorensen et al., 2020; Viana et al., 2013; Wolf et al., 2013; Yoshikawa et al., 2019). The reasoning behind the choice of allometric scaling is based on theoretical grounds as gut capacity scales linearly to body mass (BM 1.00 ) and dry matter intake to the metabolic rate (BM 0.75 ; Demment & Van Soest, 1985).…”
Section: Introductionmentioning
confidence: 99%